Prospective epidemiological study of injuries in ski and snowboard - Cumps, E.; Aerts, I.; Vandierendonck, L.; Meeusen, R. (Abstractbook. The First International Low Lands Congress on Science and Skiing, Brussels, October 11th, 2008)
This study gives a thorough descriptive overview of the injuries sustained by recreational skiers and snowboarders. However, the study is restricted by the lack of an injury definition and background information of all participating subjects. This restricts the analysis of both extrinsic and intrinsic risk factors.